Contradictions of Freedom in Student Cheating Behaviour (A Reflection on Eric Fromm's Theory): Qualitative-Descriptive Study - Maria Imakulata Tere Beding; Ignasius Ledot (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study analyzes student cheating from the perspective of Eric Fromm’s theory of freedom, focusing on the contradictions inherent in such behavior. Using a qualitative-descriptive approach, data were collected from 13 university students via purposive sampling, semi-structured questionnaires, interviews, and exam observations. Analysis followed the Miles and Huberman model. The results indicate that cheating arises from Fromm’s “contradiction of freedom,” in which the need for social attachment and the fear of alienation conflict with internal moral values such as honesty. Students choose cheating as an authoritarian escape mechanism, sacrificing autonomy to meet external expectations, which in turn triggers inner turmoil, including guilt and anxiety. The study recommends that universities establish counseling services to help students navigate these conflicts and develop a more authentic, responsible form of freedom. Keywords: contradiction of freedom, cheating, freedom according to eric fromm, attachment and isolation